PEMBERDAYAAN NILAI BUDAYA DAN KONSERVASI LEWAT PERMAINAN KOMODO TANGGA DI PULAU RINCA - Hidayat, Arif; Arfah, Muh; Mutawakkil, Ahmad; Parsi, Muhammad Jeffry; Limbong, Idem Sari; Maharani, Mega Adhwa (Jurnal AbdiMas Nusa Mandiri, 2026)
Educational games are one of the most effective innovative learning strategies for building students' understanding and awareness of cultural and environmental issues. This article discusses the representation of cultural values and conservation in Komodo Tangga, an ethnopedagogical educational game developed for elementary school students on Rinca Island, West Manggarai, East Nusa Tenggara. The purpose of this activity is to increase children's understanding of the importance of Komodo dragon (Varanus komodoensis) conservation, introduce local cultural values, and instill environmentally friendly behavior through a participatory and contextual approach. The implementation method consists of three stages: preparation, implementation, and evaluation. The activities included field observations, interviews with school partners, game trials, student pre-tests and post-tests, as well as discussion and reflection sessions with teachers and local facilitators. The evaluation results showed a significant increase in student understanding after the implementation of the Komodo Tangga game, as indicated by an increase in the average pre-test score from 54.2 to 82.5 on the post-test, covering aspects of local cultural knowledge and understanding of Komodo conservation. These findings confirm that the ethnopedagogical approach through local game media can be a community-based education model that is worth developing in other conservation areas in Indonesia. This game also has the potential to serve as a tool for cultural and environmental diplomacy to support sustainable educational tourism in the Komodo National Park area.